Enzymatic pathway for kupyaphore degradation in mycobacterium tuberculosis: mechanism of metal homeostasis and turnover - Bhosale, Rashmi S.; Chakraborty, Arnab; Wong, Tsung-Yun; Masal, Dattatraya P.; Choudhury, Rahul; Srivastava, Sonali; Reddy, D. Srinivasa; Aldrich, Courtney C.; Kamat, Siddhesh S.; Mohanty, Debasisa; Gokhale, Rajesh S. (ACS Chemical Biology, 2025)
Metallophores are essential for metal homeostasis, regulating availability, and mediating host-pathogen interactions. Kupyaphores are specialized metallophores produced by Mycobacterium tuberculosis (Mtb) that primarily chelate zinc to support bacterial survival. Elevated kupyaphore levels early in infection highlight their importance, while their rapid decline, despite increasing bacterial loads, indicates tightly regulated mechanisms of production, consumption, and degradation. However, the processes driving kupyaphore catabolism and their role in preventing zinc toxicity in Mtb remain unclear. Here, we show that covalent modification of the isonitrile moiety in kupyaphores releases zinc, triggering degradation through a sequential three-step enzymatic pathway encoded by Mtb. Isonitrile hydratase converts isonitrile groups into formamides, which are subsequently processed into amines by N-substituted formamide deformylase and ultimately oxidized to beta-ketoesters by amine oxidases. The biological significance of this pathway is underscored by the upregulation of these genes under metal-depleted and biofilm-forming conditions. Mutant Mtb strains lacking these genes exhibit impaired growth in metal-limiting environments and reduced levels of biofilm formation. Catalytic intermediates detected in Mtb cultures and infected mouse lung tissues confirm the pathway's in vivo activity. Further, genome mining reveals that similar enzymes are conserved across organisms producing isonitrile-containing metabolites, emphasizing the broader importance of this pathway. Understanding these processes could pave the way for novel therapeutic strategies targeting kupyaphore catabolism.